2009
DOI: 10.5661/bger-26-205
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transglutaminase Production: Understanding the Mechanism

Abstract: Microbial transglutaminase is an important enzyme in food processing for improving protein properties by catalyzing the cross-linking of proteins. Recently, this enzyme has been shown to exhibit wider potential application in tissue engineering, textiles and leather processing, site-specific protein conjugation and wheat gluten allergy reduction. The production of microbial transglutaminase has been significantly improved thanks to advances in bioprocess engineering and genetic engineering during the last thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…Other factors that may affect microbial growth and their metabolite products are sal t types or trace el ements and their concentrations and process conditions, including pH, temperature, dissolved oxygen, etc. Zhang et al (2009) found that transglutaminase secretion is also associated with Streptomcyes differentiation.…”
Section: Mtgase Activity Of Streptomyces Thioluteus Tta 02 Sds 14 Culmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors that may affect microbial growth and their metabolite products are sal t types or trace el ements and their concentrations and process conditions, including pH, temperature, dissolved oxygen, etc. Zhang et al (2009) found that transglutaminase secretion is also associated with Streptomcyes differentiation.…”
Section: Mtgase Activity Of Streptomyces Thioluteus Tta 02 Sds 14 Culmentioning
confidence: 99%
“…Transglutaminase activity varies depending on strain, culture medium, and cultivating condition. These strains have been used for industrial MTGase producer (Zhang et al, 2009). …”
Section: Identification Of Streptomyces Tta 02 Sds 14 Based On Sequenmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, researchers are focused on enhancement of the production of MTGase by using Streptomyces species in terms of factors affecting enzyme activity such as substrate optimization, metabolic optimization, and extrinsic factors (pH, dissolved oxygen and temperature etc.). Altering the parameters about fermentation may cause to increase the enzyme activity and hereby increasing the enzyme activity may lower the costs of the production [14]. Because of consideration in the usage of MTGase will become popular, in this study enhancement of MTGase production was investigated in terms of creating a model for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a growing number of MTGs from different microbial species were identified. Several pro-MTGs from Streptomyces have been expressed in Escherichia coli, Corynebacterium glutamicum, Streptomyces lividans, and methylotrophic yeasts (11). However, an additional protease is required to activate pro-MTG.…”
mentioning
confidence: 99%